Implementation of the Project Based-Learning Model in Dance Learning: A Study of Collaboration of Middle School Students - Puspitaloka, Wedya; Yatim, Heriyati; Nurwahidah, Nurwahidah (ETDC: Indonesian Journal of Research and Educational Review, 2024)
This study aims to measure the level of student collaboration and the effectiveness of the use of the project-based learning (PjBL) model with junior high school students.The study implements the Classroom Action Research method in two cycles, using a qualitative and quantitative approach. Each cycle includes the planning, implementation, observation, and reflection stages. The subjects of the study consisted of 29 students of class VIII.9 and the subject teacher of Arts and Culture (Dance) at public middle school 27 Makassar. The focus of the study is the application of the PjBL model to increase student collaboration in learning arts and culture (dance). Data collection techniques include observation, interviews, field notes, tests, and documentation. Data were analyzed using qualitative and quantitative analysis techniques. The results of the study showed an increase in student collaboration skills during the two learning cycles. In Cycle I, the teacher's activity sheet in teaching using the PjBL model obtained an average score of 66.6 (sufficient category), while in Cycle II it increased to 92 (very good category). Student learning activities also increased, from an average score of 60 (sufficient category) in Cycle I to 85.45 (good category) in Cycle II. The level of student collaboration increased from an average value of 68.62 (sufficient category) in Cycle I to 89.72 (very good category) in Cycle II.